ANALISIS POTENSI PERTUMBUHAN EKONOMI DI DAERAH ISTIMEWA YOGYAKARTA PADA MASA PANDEMI COVID-19 - Ary Sutrischastini; Nur Widiastuti (Buletin Ekonomi: Manajemen, Ekonomi Pembangunan, Akuntansi, 2021)
The COVID-19 pandemic has caused almost the entire world economy to decline. Likewise, the Special Region of Yogyakarta experienced a contraction in economic growth. As a result, production capacity decrease and people's welfare also decrease. This research was conducted with the aim of identifying potential business fields that can be developed (base sector) in the Special Region of Yogyakarta and calculating the amount of the multiplier so that regional economic growth can be increased again. By using Location Quotient analysis and BPS data for 2020, the results show that the Special Region of Yogyakarta has 7 basic sectors, namely the sector of providing accommodation and food and drink, the education services sector, the real estate sector, the information and communication sector, the government administration sector, defence and compulsory social security, the transportation and warehousing sector, and the water supply, waste management, waste and recycling sector. Base sector activities have a multiplier of 1.7787 to regional income. Pandemi COVID-19 mengakibatkan hampir seluruh perekonomian dunia mengalami penurunan. Demikian juga Daerah Istimewa Yogyakarta mengalami kontraksi dalam pertumbuhan ekonomi. Akibatnya kapasitas produksi menurun dan kesejahteraan masyarakat juga menurun. Penelitian ini dilakukan dengan tujuan untuk mengidentifikasi potensi lapangan usaha yang dapat dikembangkan (sektor basis) di Daerah Istimewa Yogyakarta dan menghitung besarnya multiplier agar pertumbuhan ekonomi daerah dapat ditingkatkan kembali. Dengan menggunakan analisis Location Quotient dan data BPS tahun 2020 diperoleh hasil bahwa Daerah Istimewa Yogyakarta memiliki 7 sektor basis yaitu sektor penyediaan akomodasi dan makan minum, sektor jasa pendidikan, sektor real estate, sektor informasi dan komunikasi, sektor administrasi pemerintahan, pertahanan dan jaminan sosial wajib, sektor transportasi dan pergudangan, dan sektor pengadaan air, pengelolaan sampah, limbah dan daur ulang. Kegiatan sektor basis memiliki multiplier sebesar 1,7787 terhadap pendapatan daerah.